Dysnatremia in Gastrointestinal Disorders - Do, Catherine; Evans, Gretta J.; DeAguero, Joshua; Escobar, G. Patricia; Lin, Henry C.; Wagner, Brent (Frontiers in Medicine, 2022)
The gastrointestinal and renal organ systems work in synchrony to absorb necessary nutrients and water and to excrete waste products. The gastrointestinal absorptive and secretory functions enable food digestion and water absorption needed to sustain life. Homeostasis is maintained by the kidneys. Gastrointestinal perturbations including vomiting and diarrhea can lead to significant volume and electrolyte losses, overwhelming the renal homeostatic compensatory mechanisms. Dysnatremia, potassium and acid-base disturbances can result from gastrointestinal pathophysiologic processes.